Current classifications of muscle injuries: strengths and limitations - E. N. Bezuglov; V. Yu. Khaitin; O. A. Etemad; E. O. Lebedenko; A. P. Grinchenko; A. M. Filimonova (Спортивная медицина: наука и практика, 2024)
Introduction: Despite the large number of classifications of muscle injuries proposed by different expert groups, there is still no classification that can fully satisfy the requirements of practitioners in terms of predicting the duration of treatment and minimising the risk of recurrence. At the same time, the diversity of classifications may lead to different interpretations of the severity of the same injury with subsequent variability in the choice of rehabilitation protocol and its duration.Aim: to analyse the advantages and disadvantages of the most common classifications of muscle injuries in the practice of professionals working with athletes.Materials and methods: The Pubmed and Google Scholar databases were searched for articles in English describing classifications of muscle injuries proposed since 2000. The following word combinations were used for the search: ‘classification of muscle injuries’, ‘grading of muscle injuries’, ‘muscle damage’ and ‘muscle injuries’. The study design was a narrative review.Results: Eight classifications proposed by different expert groups since 2000 were found. The Munich Consensus and British Athletic Association classifications of muscle injuries and the MLG-R classification can be considered the most commonly used at present, based on various combinations of clinical symptomatology, mechanism of injury and localisation, and magnetic resonance imaging findings.Conclusion: There are currently several of the most widely used classifications of muscle injuries, and communities of practice should appreciate this diversity when determining injury severity and predicting treatment time, and use the same classification.